INTENSIVE PARENTING TRAINING AND BASED ON CHILDREN PROTECTION IN THE COMMUNITY OF BLITAR REGENCY - Zuhdi, Muhammad Sholihuddin (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2019)
In this era, there are many parents who are too busy to work with the aim of meeting their daily needs and social demands, in the end there are some parents who neglect their children or often scold their children because they feel tired from their work. Improper treatment of children will have a negative impact on children. In this paper we will discuss parenting training for parents who have difficulty in caring for children. The method used is the Rapid Rural Appraisal (RRA) method is a method in advancing the situation and conditions in an area (rural or urban), a fast step here is to find data and information quickly from various sources In this service, data and information were obtained from the community, the child protection commission in the Wonodadi sub-district, and influential figures in the Pikatan village community. The result of the training is that there are changes in parents who initially have an authoritarian parenting gradually improve and apply parenting according to the needs of the child.